Voltage control in distribution feeders with high penetration of wind energy (2017)
The recent drift towards balancing generation and consumption, along with increasing demands of high power quality and reliability, require the deployment of energy storage and application of demand response in the smart grid. The potential for using energy storage and demand response promise to have a major impact on schemes for voltage control in a smart grid. This paper presents a comprehensive optimisation architecture that do not only take into consideration the coordination of VAr control devices, but also manages storage facilities and demand response in an hourly operation fashion. An integrated framework on hybrid Particle Swarm Optimisation/Gravitational Search Algorithm (PSOGSA) is used for VAr control devices, energy storage and demand response optimisation scheduling. The effectiveness of the proposed method is validated through a quasi-time sequence analysis over a 24-hourly simulation period. Test results show that the smart coordinated operation among the control devices causes reduction in system losses and enhances system capability to maintain voltages within the prescribed bounds.